KITAB TAREKAT SYATTARIYAH: Sumber Doa dan Wirid dalam Tradisi Sufi Indonesia - Hilyana Nabila; Durrotun Humaira (EL-ADABI : Jurnal Studi Islam, 2025)
This research examines the Syattariyah Congregation in Indonesia. The starting point for the research began with an analysis of the manuscript of the Syattariyah Tarekat Book found in Cirebon, West Java. The aim of this research is to (1) analyze the overall outline of the contents of the Syattariyah Tarekat manuscript; (2) examine the history and influence of the Syattariyah Tarekat; and (3) explaining the contribution of the Syattariyah Tarekat to the local Sufi tradition. The research method used is descriptive analysis, which describes the research object according to the data without changing it. To collect research data using literature studies. From the results of this analysis, research results were obtained in the form of: (1) The overall outline of the 36-page manuscript of the Syattariyah Tarekat Book contains prayers, dhikr and wird of the Syattariyah Tarekat, readings about the intention to enter the Syattariyah Tarekat, as well as the meaning of syahadatain; (2) The Syattariyah Tarekat originated in India in the 15th century, founded by Abdullah ash-Syattar, brought to Indonesia by Sheikh Abdur Rouf as-Singkili. This order plays an important role in Islamic da'wah which teaches spiritual values ​​and character through village recitations; (3) The Syattariyah Tarekat is accepted by the community because its teachings are easy to implement and blend with local culture, teaching spiritual values ​​through organized Sufism education.